Fast Consensus of Networked Multiagent Systems with Two-Hop Network. (16th September 2015) - Gao, Jinfeng; Bu, Bin; Feng, Lihui; Gu, Minming
Abstract : This paper studies the consensus convergence speed of multiagent systems (MASs) from two aspects including communication topology and the state of agents. Two-hop network is considered in the communication topology. A novel consensus protocol that includes the information of the states motions and their integrals is introduced. And the protocol has much faster convergence speed by choosing some appropriate weight values. The protocol can be applied to distributed control and large-scale systems. A numerical example is presented to illustrate the effectiveness and superiority of the proposed method.